A trajectory study of postoperative frailty and cognitive function in elderly spinal surgery patients: a cohort study in China - Li, Rui; Deng, Qian; Peng, Cheng; Song, Hong; Shan, Xiaotian; Wang, Yao; Jin, Chunyan (Frontiers in Aging Neuroscience, 2025)
ObjectiveTo explore the developmental trajectory of postoperative frailty and cognitive function in elderly spinal surgery patients and the predictive relationship between the two.MethodsA total of 266 elderly individuals were selected as the study subjects, and their debilitation and cognitive functions were tracked and investigated at T1 (at the time of discharge from the hospital), T2 (at 3 months postoperatively), and T3 (at 6 months postoperatively), and the data were analyzed using cross-lagged model and latent variable growth model.ResultsThe latent variable growth model showed a decreasing trend in frailty (S = −0.197, p = 0.013) and an increasing trend in postoperative cognitive function (S = 0.124, p = 0.002) from T1 to T3 in elderly spinal surgery patients; at the initial level, frailty was negatively correlated with cognitive function (r = −0.452, p < 0.001), and initial levels of frailty negatively predicted the self development rate (β = −0.516, p < 0.001), the initial level of frailty negatively predicted the development rate of postoperative cognitive function (β = −0.321, p = 0.003), and the initial level of postoperative cognitive function positively predicted the development rate of frailty (β = 0.192, p = 0.031).ConclusionElderly spinal surgery patients showed a decreasing trend of postoperative frailty and an increasing trend of postoperative cognitive function, frailty and postoperative cognitive function at the initial level had a mutual predictive effect, the initial level of frailty was able to negatively predict the rate of development of their own and postoperative cognitive function, and the initial level of postoperative cognitive function was able to positively predict the rate of development of frailty.